Development of a laser capture microscope-based single-cell-type proteomics tool for studying proteomes of individual cell layers of plant roots. (1st June 2016) - Zhu, Yingde; Li, Hui; Bhatti, Sarabjit; Zhou, Suping; Yang, Yong; Fish, Tara; Thannhauser, Theodore W
Abstract: Single-cell-type proteomics provides the capability to revealing the genomic and proteomics information at cell-level resolution. However, the methodology for this type of research has not been well-developed. This paper reports developing a workflow of laser capture microdissection (LCM) followed by gel-liquid chromatography-tandem mass spectrometry (GeLC-MS/MS)-based proteomics analysis for the identification of proteomes contained in individual cell layers of tomato roots. Thin-sections ( 10-μm thick, 10 sections per root tip) were prepared for root tips of tomato germinating seedlings. Epidermal and cortical cells (5000–7000 cells per tissue type) were isolated under a LCM microscope. Proteins were isolated and then separated by SDS–polyacrylamide gel electrophoresis followed by in-gel-tryptic digestion. The MS and MS/MS spectra generated using nanoLC-MS/MS analysis of the tryptic peptides were searched against ITAG2.4 tomato protein database to identify proteins contained in each single-cell-type sample. Based on the biological functions, proteins with proven functions in root hair development were identified in epidermal cells but not in the cortical cells. Several of these proteins were found in Al-treated roots only. The results demonstrated that the cell-type-specific proteome is relevant for tissue-specific functions in tomato roots. Increasing the coverage of proteomes and reducing the inevitable cross-contamination from adjacent cell layers, in both vertical and cross directions when cells are isolated from slides prepared using intact root tips, are the major challenges using the technology in proteomics analysis of plant roots. Abstract : Plant cell function: Microscope method picks out proteins A high-tech method of microscopy using lasers enables scientists to study the protein characteristics of individual cells. The US team of researchers, led by Suping Zhou of Tennessee State University and Theodore Thannhauser of Cornell University, examined proteins in tomato root cells. Using laser capture microscopy (LCM), they isolated cells from root layers that may be only one cell layer thick. Proteins were extracted from the cells, separated into types, and their functions ascertained by matching to known proteins. Comparing cells from different root layers under normal and aluminum-stressed condition, the team identified clear differences in protein content. Although LCM is at present time-consuming and costly, this 'proof of concept' suggests that, as technology advances, it could have broad application for studying the relationships between proteins and cell function.